Inducing puberty in beef heifers with hormones - DeBenedetti, R.; Kiracofe, G.H.; Hultine, V.; McKee, R.M.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-six Polled Hereford and Simmental-cross heifers that had not cycled by the beginning of the breeding season were given an ear implant and injected with an estrogen-progestogen compound. The implant was removed after 9 days and all heifers were in estrus 1 to 5 days later. Six heifers conceived the first insemination, 11 the second, and 24 during the 65-day breeding season.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Hormones; Implant; Synchronize